Type of sport is related to injury profile: A study on cross country skiers, swimmers, long-distance runners and soccer players. A retrospective 12-month study - Ristolainen, L.; Heinonen, A.; Turunen, H.; Mannström, H.; Waller, B.; Kettunen, J. A.; Kujala, U. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This 12-month retrospective questionnaire compared the occurrence of sports injuries in 149 cross country skiers, 154 swimmers, 143 long-distance runners and 128 soccer players aged 15-35 years. Soccer had significantly more injuries (5.1 injuries/1000 exposure hour) than other sports (2.1-2.8, P<0.001). More runners than soccer players reported overuse injuries (59% vs 42%, P=0.005), locating typically in the foot in runners, soccer players and skiers. Swimmers reported overuse injuries in the shoulder more commonly than skiers (40% vs 1%, P<0.001), who also intensively load shoulders. Acute injuries in skiers (80%) and in swimmers (58%), and overuse injuries in skiers (61%), occurred during exercise other than own event. In soccer and running the absence time from sport because of injuries was significantly longer than in skiing and swimming. No severe permanent disabilities occurred due to injury but seven women quit sports because of injury. In conclusion, type of loading is strictly associated with the anatomical location of an overuse injury as shown by the difference in shoulder injury incidence between swimmers and cross country skiers. In some sports, a significant proportion of acute injuries occur in other than the main event.